2022
DOI: 10.3390/antibiotics11040496
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of a Panton–Valentine Leukocidin-Positive ST22 Community-Acquired Methicillin-Resistant Staphylococcus aureus from Pakistan

Abstract: Staphylococcus aureus (S. aureus) ST22 is considered a clinically important clone because an epidemic strain EMRSA-15 belongs to ST22, and several outbreaks of this clone have been documented worldwide. We performed genomic analysis of an S. aureus strain Lr2 ST22 from Pakistan and determined comparative analysis with other ST22 strains. The genomic data show that Lr2 belongs to spa-type t2986 and harbors staphylococcal cassette chromosome mec (SCCmec) type IVa(2B), one complete plasmid, and seven prophages or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
(77 reference statements)
1
4
0
Order By: Relevance
“…However, in the present study, only a total of 21 isolates (23.9%) harbored the lukED genes, which were distributed among various sequence types (ST1: n = 5, ST88: n = 1, ST239: n = 2, ST672: n = 10, ST1178: n = 1, ST7879: n = 1, ST7883: n = 1). In addition, the lukED genes were not found in the ST22 isolates, which was consistent with a previous study 52 . Despite recent findings which described the emergence of hypervirulent ST22 strains carrying both PVL and tst genes 53 , 54 , the HSNZ ST22 isolates notably lacked these virulence factors.…”
Section: Discussionsupporting
confidence: 92%
“…However, in the present study, only a total of 21 isolates (23.9%) harbored the lukED genes, which were distributed among various sequence types (ST1: n = 5, ST88: n = 1, ST239: n = 2, ST672: n = 10, ST1178: n = 1, ST7879: n = 1, ST7883: n = 1). In addition, the lukED genes were not found in the ST22 isolates, which was consistent with a previous study 52 . Despite recent findings which described the emergence of hypervirulent ST22 strains carrying both PVL and tst genes 53 , 54 , the HSNZ ST22 isolates notably lacked these virulence factors.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, El-Deeb et al [ 73 ] analyzed the whole genome of nine methicillin-resistant staphylococci (MRS) collected in Eastern Province, Saudi Arabia, and they found that only isolate SA1 recovered from goat’s milk had the PVL toxin gene and the Staphylococcus enterotoxin B gene seb . Ullah et al [ 70 ] conducted a genomic investigation of an S. aureus strain isolated from Pakistan and discovered that the strain has many prophage-associated virulence factors, including PVL and toxic shock syndrome toxin (TSST). Additionally, all 52 isolates of S. aureus isolated from the vascular accesses in hemodialysis patients at Assiout University Hospitals were negative for the PVL gene [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Each row represents the aligned sample. Panton-Valentine leukocidin (PVL) toxin is a virulence factor in S. aureus associated with deep skin and soft-tissue infections (furunculosis, cutaneous abscesses, and severe necrotizing pneumonia) [68][69][70]. In 1932, Panton and Valentine defined the PVL as a virulence factor in the family of synergohymenotropic toxins in S. aureus [71].…”
Section: Core Genesmentioning
confidence: 99%
“…This collection also gathers papers on antibiotic resistance of some of the major emerging infections pathogens such as Mycobacteroides abscessus [ 3 ], Klebsiella pneumoniae [ 4 , 5 ], Salmonella sp. [ 6 , 7 ], Francisella tularensis [ 8 ], Acinetobacter baumannii [ 9 , 10 ], or Pseudomonas aeruginosa [ 11 ] and other human pathogens such as Neisseria gonorrhoea [ 12 ], Staphylococcus aureus [ 13 ], or Escherichia coli [ 14 ]. Most of them are high-priority pathogens [ 15 ], according to the National Institute of Allergy and Infectious Diseases, and are globally and medically important pathogens.…”
mentioning
confidence: 99%
“…It has been classified as a globally and medically important human and foodborne pathogen [ 16 ], and methicillin resistance has been a major challenge to treatment and patient science. Ullah et al have performed a comparative genomic analysis of a highly virulent methicillin-resistant S. aureus (MRSA) of a Pakistan clone [ 13 ].…”
mentioning
confidence: 99%